2018
DOI: 10.1177/1055665618820754
|View full text |Cite
|
Sign up to set email alerts
|

Parent Perceptions of Initial Feeding Experiences of Children Born With Cleft Palate in a Rural Locale

Abstract: Background and Hypothesis: An early problem frequently present in infants born with cleft lip (CL), cleft lip and palate (CLP), or cleft palate (CP) is difficulty feeding. In many cases, health-care professionals are not familiar with the appropriate feeding techniques and unable to instruct parents correctly. This problem can be particularly significant in rural areas where health-care resources are limited and children with clefts are seen on an infrequent basis. The purpose of the investigation was to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
0
17
1
Order By: Relevance
“…There is some evidence suggests that guidance specific to feeding can reduce rates of NICU admission, when feeding is the sole concern, among infants with CLP (Hubbard et al, 2012). However, there is some evidence that hospitals’ nursing staff have limited knowledge of the consequences of CLP and associated feeding issues (Snyder et al, 2019; Madhoun et al, 2020), resulting in mothers not receiving adequate training on adapted feeding approaches. Collectively, this reality has the possibility of contributing to a reduction in successful human milk feeding.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence suggests that guidance specific to feeding can reduce rates of NICU admission, when feeding is the sole concern, among infants with CLP (Hubbard et al, 2012). However, there is some evidence that hospitals’ nursing staff have limited knowledge of the consequences of CLP and associated feeding issues (Snyder et al, 2019; Madhoun et al, 2020), resulting in mothers not receiving adequate training on adapted feeding approaches. Collectively, this reality has the possibility of contributing to a reduction in successful human milk feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding a CL/P infant can be time consuming and it can lead to maternal/parental stress and anxiety (Snyder & Ruscello, 2019), as well as communication, emotional, and social problems (Nelson et al, 2012). But mother–infant bonding is enhanced (Gailey, 2016) by the proximity of feeding at the breast.…”
Section: Discussionmentioning
confidence: 99%
“…Peer support groups for mothers with CL/P who have experience breastfeeding are essential (Santos et al, 2019), but lacking. Parents have reported gaps in health care providers’ (HCP) knowledge (Snyder & Ruscello, 2019). HCP who do not have enough breastfeeding clinical experience will provide inaccurate information to mothers (Lindberg & Berglund, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is evidence that information given to parents regarding feeding instruction is lacking due to hospital personnel having limited or no experience in the area of cleft palate feeding management. 18 Snyder and colleagues (2019) surveyed parents of infants with cleft lip and palate regarding perceptions of feeding experiences during the initial evaluation and found that 69% of parents received feeding information at the birth hospital, 4% received information prior to the birth of their child, and 15% received no information at all. 18 Additionally, course-based instruction for low-incidence disorders, such as cleft palate, receives less focus within training programs.…”
Section: Introductionmentioning
confidence: 99%